Comparison Between the BOQ of Conventional and BIM Method on BPJS Building in Central Jakarta - Mutia Hanuun Ufaira Akbar; I Ketut Sucita; Erlina Yanuarini (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
In the construction planning process, the calculation of the quantity of each project work was packaged in a Bill of Quantity (BoQ) to complete the project and greatly affected the continuity of the entire construction construction process. With advances in technology in the world of construction, it could simplify planning in built a building and could increased the accuracy of calculations without using assumptions that could increased the volume of work. One of the results of current technological advances was the creation of the Building Information Modeling (BIM) method, a method that was able to simulate all information in a development project into a 3-dimensional model. Currently the use of the BIM method in Indonesia was still limited so that in this research, the aim was to determine the effectiveness of the use of BIM on the accuracy calculation of the volume of the BoQ and to know the percentage comparison. The building project that was used as a comparison was a building with the middle rise building category, namely the Central Jakarta BPJS Building. Based on the research conducted, it was found that the difference between conventional and BIM results on pilecap components was 5%, column 6%, beam 35%, floor slabs 2%, stairs 22%, ceiling 2.26% floor coverings 14% lower than conventional calculations but for the wall component the BIM calculation is 0.78% greater than the conventional calculation. So that the total percentage ratio is 10%, thus this proves that the use of the BIM method in calculating quantity was effective in terms of calculation accuracy.